The Trend of Consumptive Behavior Among Accounting Education Students: Exploring The Influence of Influencer Marketing, FoMO, and Brand Awareness - Nurfatimah, Fitri; Jatmika, Surya (Universitas Hamzanwadi, 2024)
Consumptive behavior among students is evident in their tendency to purchase items that are not necessary, often influenced by the appearance of an influencer, FoMO, and their brand awareness of products marketed by influencers. The aim of this research is to investigate the influence of influencer marketing, FoMO, and brand awareness on the consumptive behavior of Accounting Education students at Muhammadiyah University of Surakarta. This research is a comparative causal study with a quantitative approach. The sample consists of 134 respondents and data collection was done using questionnaires. The data were analyzed using multiple linear regression analysis. The results of this study indicate that consumptive behavior is positively and significantly influenced by influencer marketing, the FoMO, and brand awareness of Accounting Education students at Muhammadiyah University of Surakarta, with an effective contribution of 26,88%, 8,32%, dan 12,75%. The coefficient of determination in this study is 48,0%.